2021
DOI: 10.5114/aoms.2020.92860
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-107 promotes apoptosis of acute myelocytic leukemia cells by targeting RAD51

Abstract: Introduction: This study aimed to investigate the role of microRNA (miRNA) that affects acute myelocytic leukemia (AML) and its potential molecular mechanism by constructing a miRNA-mRNA interaction network using bioinformatics methods. Material and methods: MicroRNA expression data of AML were retrieved from Gene Expression Omnibus (GEO) and analyzed by microarray analysis. Expression levels of miR-107 and RAD51 mRNA were detected by quantitative real time polymerase chain reaction (qRT-PCR). Protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Te number of invasive cells was lower in the miR-107 inhibitor group than in the blank and control miRNA groups, but there was no signifcant diference between the b groups. Furthermore, this shows that inhibiting miR-107 has a considerable inhibitory impact on it; confrming those fndings, researchers anticipate that by changing tumor cells into cells that support parenchymal cells in the completion of organ tasks, miR-107 will boost cell invasion and metastasis in breast cancer cell lines [19,20]. In addition, it is well known that in the biological behavior of cells, there is an indicator that can signifcantly monitor the degree of cell damage, namely apoptosis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Te number of invasive cells was lower in the miR-107 inhibitor group than in the blank and control miRNA groups, but there was no signifcant diference between the b groups. Furthermore, this shows that inhibiting miR-107 has a considerable inhibitory impact on it; confrming those fndings, researchers anticipate that by changing tumor cells into cells that support parenchymal cells in the completion of organ tasks, miR-107 will boost cell invasion and metastasis in breast cancer cell lines [19,20]. In addition, it is well known that in the biological behavior of cells, there is an indicator that can signifcantly monitor the degree of cell damage, namely apoptosis.…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that miR-107 inhibition affects breast cancer cell growth and apoptosis. Breast cancer cells may be inhibited from autophagy, proliferation, and migration by HMGB1 [ 17 ]; in addition, several research studies have discovered that miR-107 controls PTX sensitivity via Wnt/-catenin signaling pathway, which targets TPD52 [ 18 – 20 ], [ 17 , 18 , 18 – 20 ]. The most dangerous and life-threatening behavior of cancer cells is invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, these apoptosis-related genes participate in the regulation of apoptosis, the JAK-STAT signaling pathway, the FoxO signaling pathway, the PI3K-Akt signaling pathway, the TNF signaling pathway, and other signaling pathways (Figure S19). It has been reported that miR-103a-3p and miR-107-3p are involved in the regulation of apoptosis [62,63]. Both chi-miR-103-3p and chi-miR-107-3p are in the ceRNA network related to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are non-protein-coding RNAs that are longer than 200 nucleotides [6,7]. LncRNAs have been confirmed to play a key role in an increasing number of diseases [8][9][10]. Although many lncRNAs have been found to be involved in atherosclerosis, compared with coding molecules, a relatively small number of genes has been studied.…”
Section: Introductionmentioning
confidence: 99%